Lean Condition Procedure for Utilization of Silica from Rice Husk as Zeolite Precursor - Winarto Kurniawan; Hirofumi Hinode (Faculty of Engineering and Technology, Sampoerna University, 2020)
Rice husk is rich in Si that makes it applicable as Si source for zeolite synthesis. However, the conventional method to use rice husk as a zeolite precursor has some drawbacks, which are: Si recovery method that involves burning and causing air pollution and carbon resources loss; and the use of severe conditions and sophisticated apparatuses which are not suitable for rural application where rice husk is mainly produced. In this paper, a method to prepare rice husk as zeolite Si source via a non-combustion process was proposed. Furthermore, its utilization as a zeolite precursor via moderate condition was also investigated. Si was recovered directly from rice husk using a sodium hydroxide solution. Si was successfully recovered from rice husk, and the optimum condition for recovery was found to be 1 N of NaOH and 16 hours of contact time. The application of the recovered Si for zeolite precursor at moderate condition was successful, and it was able to produce a product rich in zeolite P and zeolite X depending on the condition. Among zeolites synthesized in this experiment, the sample prepared by treatment time of 15 hours showed the highest cation exchange capacity, which makes it a promising material to be used as an ion-exchange agent.